Analysis of the Effect of Black Garlic (Allium sativum) Extract on Ovarian Follicular Atresia, Endometrial VEGF Expression, and Fallopian Tube Epithelial Cell Count in Rats (Rattus norvegicus) Exposed to Cigarette Smoke - Kridayanti, Novalia; Anandasari , Noni Fidya Ayu; Kaspirayanthi, Ni Ketut Devy; Nurseta, Tatit; Raras, Tri Yudani Mardining; Khotimah, Husnul; Reksohusodo, Subandi; Angelica, Aina; Anita, Kenty Wantri; Yudhanto, Hendy Setyo (JURNAL INFO KESEHATAN, 2024)
Cigarette smoke exposure significantly impairs reproductive function in Rattus norvegicus. This study evaluated the protective effects of black garlic extract against such damage. Using a post-test-only control group design, 25 female Wistar rats were divided into five groups and exposed to cigarette smoke with or without varying doses of black garlic extract. After four weeks, results indicated that black garlic extract significantly increased Vascular Endothelial Growth Factor expression, enhanced fallopian tube secretory epithelial cell counts, and reduced ovarian follicular atresia in rats exposed to cigarette smoke. The group receiving 50 mg/kgBW of black garlic extract showed the most significant improvements. Statistical analysis, including One-way ANOVA, revealed significant differences between groups. Normality was assessed using the Shapiro-Wilk test, and homogeneity was confirmed with the Levene test. Significant decreases in ovarian follicular atresia (p < 0.05) and increases in Vascular Endothelial Growth Factor expression (p < 0.05) and secretory epithelial cell counts (p < 0.05) were observed in the 50 mg/kgBW treatment group compared to controls. In conclusion, black garlic extract offers dose-dependent protection against cigarette smoke-induced reproductive damage, with 50 mg/kgBW being the optimal dose. Further research should explore molecular mechanisms, long-term toxicity, and clinical applications in humans.